FINANCIAL FEASIBILITY OF RICE RED RICE FARMING Oryza nivara (CASE STUDY: VILLAGE OF SARAN PADANG , DOLOK SILAU SUBDISTRICT, SIMALUNGUN REGENCY) - Ira Apriyanti; Gustina Siregar; Marlina Ariani Dalimunthe (JASc (Journal of Agribusiness Sciences), 2017)
This research was conducted with the aim to know the financial feasibility of red rice farming. The population in this study is farmers of red rice in the village of Saran Padang, Dolok Silau District, Simalungun Regency. From the research results obtained the amount of rice production of red rice amounted to 1,014.40 Kg with the price of Rp. 5,700 / Kg, then the amount of farmer's acceptance is Rp. 5,782,080 seasonal crops. Total cost incurred of Rp. 2.851.535 planting season, so that the income of Rp. 2,930,545. Red rice farming is feasible to be cultivated based on NPV, IRR and BEP criteria with NPV value 11.251.995, IRR value is 76,76%, and BEP value is overall profitable, with BEP value Rp. Rp. 2.811 BEP Production 287,87 Kg and BEP Revenue Rp. 1.640.213.Keywords: Financial Feasibility, Rice Red, Farming